2007
DOI: 10.1016/j.mbs.2007.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimal mix of screening and contact tracing for endemic diseases

Abstract: Two common means of controlling infectious diseases are screening and contact tracing. Which should be used, and when? We consider the problem of determining the cheapest mix of screening and contact tracing necessary to achieve a desired endemic prevalence of a disease or to identify a specified number of cases. We perform a partial equilibrium analysis of small-scale interventions, assuming that prevalence is unaffected by the intervention; we develop a full equilibrium analysis where we compare the long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…The smaller the number of untreated infections, p ( s ), and the greater the screening cost, c s , the larger the role of contact tracing in identifying people for treatment. This is analogous to a result of Armbruster and Brandeau (2007b) who considered the optimal mix of screening and contact tracing to reduce the prevalence of a curable endemic disease (assuming that contact tracing has fixed efficacy (i.e., that κ is constant)): they found that contact tracing was part of the cost-minimizing solution only when the prevalence of the disease was below a given threshold.…”
Section: Model Of a Chronic Viral Diseasesupporting
confidence: 53%
See 1 more Smart Citation
“…The smaller the number of untreated infections, p ( s ), and the greater the screening cost, c s , the larger the role of contact tracing in identifying people for treatment. This is analogous to a result of Armbruster and Brandeau (2007b) who considered the optimal mix of screening and contact tracing to reduce the prevalence of a curable endemic disease (assuming that contact tracing has fixed efficacy (i.e., that κ is constant)): they found that contact tracing was part of the cost-minimizing solution only when the prevalence of the disease was below a given threshold.…”
Section: Model Of a Chronic Viral Diseasesupporting
confidence: 53%
“…Their models bear some similarity to our model except that our model is complicated by the presence of additional states, the lack of a cure, and contact tracing as a second control in addition to screening. Armbruster and Brandeau (2007b) used an optimal control approach to find the best combination of screening and contact tracing to control an infectious disease. They examined a curable endemic disease (instead of a chronic one as we do here) and assumed that contact tracing has a fixed efficacy, if it is performed at all.…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the benefit of averting each additional infection is the same as the benefit of averting any other infection, so the marginal benefit equals the average benefit. The concept of marginal benefit (and thus benefit) is equivalent to the cost-effectiveness threshold (in terms of dollars per life year or quality-adjusted life year of survival gained) used implicitly or explicitly in many cost-effectiveness analyses of HIV prevention programs [5, 6, 23-27]: it is the level of benefit the prevention program must have in order to be considered cost effective.…”
Section: Model Frameworkmentioning
confidence: 99%
“…(3) Given these costs, a single DU chooses the screening level that minimizes its net present value of discounted future costs. We solve for the symmetric, pure-strategy Nash equilibrium.…”
Section: Methodsmentioning
confidence: 99%